Inhibiting the HPV16 oncogene-mediated glycolysis sensitizes human cervical carcinoma cells to 5-fluorouracil - Ma, Dan (Onco Targets Ther, 2019)
BACKGROUND: Human papillomavirus (HPV), the major cause of cervical cancer worldwide, is associated with infection of HPV (Oncogenic HPV). Cancer patients who develop drug resistance are resulted in failure of chemotherapy. OBJECTIVE: We investigated the mechanisms for the HPV E6/E7 oncoprotein-mediated 5-fluorouracil (5-Fu) sensitivity. METHODS: HPV-16 E6/E7 was transfected into human cervical cancer cell lines. Glycolysis rate was assessed. Xenograft model was established to examine the in vivo therapeutic effects of E6/E7 inhibition and 5-Fu treatments. RESULTS: The HPV-16 E6/E7 oncoprotein induces 5-Fu resistance in cervical cancer cells. Overexpression of E6/E7 renders CaSki and SiHa cells resistant to 5-Fu treatments. We found E6/E7 expressions were significantly upregulated in 5-Fu-resistant cells compared with parental cells. Moreover, the cellular glycolysis rate was significantly increased in 5-Fu-resistant cells. The glucose uptake, lactate production, and expressions of glycolysis enzymes were upregulated in 5-Fu-resistant cells. We report the E6/E7-mediated 5-Fu resistance was through upregulation of glycolysis pathway. Importantly, inhibition of E6/E7 by shRNA effectively decreased cellular glycolysis and overcame 5-Fu resistance using in vitro and in vivo xenograft model. CONCLUSION: Our study contributed to understanding the molecular mechanisms for HPV E6/E7-mediated 5-Fu resistance and development of new therapeutic strategies against cervical cancer.